2009
DOI: 10.1016/j.rmed.2008.12.015
|View full text |Cite
|
Sign up to set email alerts
|

High resolution computed tomography and pulmonary function in common variable immunodeficiency

Abstract: Patients with common variable immunodeficiency (CVID) have impaired production of immunoglobulins and hence recurrent airway infections, which in turn may lead to radiological changes and impaired lung function. Uncertainty exists about the nature and frequency of the radiological and the physiological abnormalities, and how they relate to each other. We reassessed high resolution computed tomography (HRCT) images in 65 patients, reported results from previously measured lung function tests, and studied relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 27 publications
7
32
1
2
Order By: Relevance
“…For air trapping, we demonstrated that visual, as well as quantitative, HRCT measurements correlate significantly with PFTs and disease duration. For visual scoring of air trapping, previous studies have also found a significant correlation with PFTs in CVID patients [20]. These data and our data indicate that HRCT-diagnosed air trapping is related to relevant airway obstruction in these patients.…”
Section: Discussionsupporting
confidence: 85%
“…For air trapping, we demonstrated that visual, as well as quantitative, HRCT measurements correlate significantly with PFTs and disease duration. For visual scoring of air trapping, previous studies have also found a significant correlation with PFTs in CVID patients [20]. These data and our data indicate that HRCT-diagnosed air trapping is related to relevant airway obstruction in these patients.…”
Section: Discussionsupporting
confidence: 85%
“…In patients with primary or secondary immunodeficiency, replacement therapy with IgG effectively prevents severe systemic infection. However, despite appropriate IgG supplementation, frequently occurring chronic infection/inflammation of the respiratory and gastrointestinal mucosae has been linked to low serum IgA levels (42)(43)(44). The inherent structural features of SIgA would make it a logical agent to fill this therapeutic gap in combination with standard therapy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 65 patients, correlation was found between bronchial wall thickening, mucoid impaction and mosaic lung attenuation on the one hand and airway obstruction (FEV1 and FEV1/FVC) on the other [167]. Low diffusing capacity of the lung for carbon monoxide (DLCO) was associated with bronchial wall thickening and linear opacities.…”
Section: Bronchiolitis Obliterans After Lung Transplantationmentioning
confidence: 96%